Rancang Bangun Sistem Penelusuran Minat Dengan Tes The Rothwell Miller Interest Blank (RMIB) Berbasis Web - Suviani, Nita; Sunarto, M. J. Dewiyani; Amelia, Tan (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2012)
RMIB is a test designed to measure people's interest based on their attitude towards a job. This method is combining people's intellectual ability (skill) with interest and talent, this method could help them discovering a suitable job based on their interest and talent. However, there are some obstacles when the psychologist will apply this method, such as; number of participant, time and place if they are from different city. Therefore, an application has been designed in order that the psychologist can find it easier when they are doing the test. As a result, the clients coming from other cities or other islands can take a part on the test . From 10 people including the respondent and the psychologist, 80% of them stated that they are agree with the existence of this application. This application is completely helpful and easy to use. Moreover, it is supported with chatting facility which simplifies the consultation process in which the client is able to consult the psychologist indirectly or without face-to-face activity. Keywords: Minat , RMIB.